Evaluation of Impact of Pregnancy on Oral Health Status and Oral Health Related Quality of Life among Women of Kashmir Valley - Shah, Aasim Farooq (J Clin Diagn Res, 2017)
INTRODUCTION: Oral health is a key component of overall health and wellbeing of women throughout life; and particularly important prior to conception and during pregnancy. Pregnancy affects both general health as well as the oral health related quality of life. AIM: To assess the difference in oral health status and related quality of life among pregnant, postpartum and non pregnant women of Kashmir valley. MATERIALS AND METHODS: The present cross-sectional study was conducted among a convenient sample of 900 women (22-37 years) attending Sheri-Kashmir Institute of Medical Sciences (SKIMS) Maternity Hospital, Srinagar, Jammu and Kashmir, India. Sample included 300 pregnant, 280 postpartum women and 320 non pregnant women of matched age group. Pretested and validated proforma for Oral Health Related Quality of Life (OHRQoL) Questionnaire designed in local language was used. Oral health was assessed using Oral Hygiene Index Simplified Index (OHIS), Gingival Index (GI) and Decayed Missing Filled Teeth/Surface Index (DMFT/DMFS). Mean differences were carried out using Kruskal-Wallis one-way ANOVA. Correlation analysis was performed to analyse their relationship with Oral Health Impact Profile (OHIP-14) score. Post-hoc Tukey test was employed for comparing the means within the three trimesters of the pregnant group. RESULTS: Pregnant women presented with significantly higher periodontal disease (p≤0.05). Decayed Missing and Filled Teeth index (DMFT) showed no difference within the groups. Comparison for the mean OHIP-14 presented significantly poorer scores among the pregnant women. CONCLUSION: Pregnancy had an influence only on the gingiva and not on periodontal attachment levels. However, oral health status and perceived OHRQoL were poorer among pregnant women. The present study draws attention toward the need for highlighting the importance of conserving oral health during pregnancy.